Assessing vegetation indices and productivity across nitrogen gradients: a comparative study under transplanted and direct-seeded rice - Chowdhury, Manojit; Khura, Tapan Kumar; Upadhyay, Pravin Kumar; Parray, Roaf Ahmad; Kushwaha, H. L.; Singh, Chandu; Lama, Achal; Mani, Indra (Frontiers in Sustainable Food Systems, 2024)
Nitrogen responses vary under diverse agronomic management practices, influencing vegetation indices (VIs) and productivity across different ecological conditions. However, the proper quantification of these responses under various crop establishment methods with varied nitrogen levels is rarely studied. Therefore, a field experiment was conducted to investigate the impact of varying nitrogen levels on VIs, growth parameters, yield attributes, yield, and economic aspects of transplanted rice (TR) and direct-seeded rice (DSR). The experiment was conducted in the randomized block design consisted seven N levels, which included 0% recommended dose of nitrogen (RDN) or no nitrogen (N0), 33.33% RDN (N1), 66.66% RDN (N2), 100% RDN (N3), 133.33% RDN (N4), 166.66% RDN (N5) and 200% RDN (N6), and replicated thrice. The plots with higher N levels demonstrated increased values of VIs and treatment N3 (120 kg N ha-1), N4 (160 kg N ha-1), N5 (200 kg N ha-1), and N6 (240 kg N ha-1) showed no statistically significant differences in NDVI (normalized difference vegetation index), RVI (Ratio vegetation index), NDRE (normalized difference red edge), and GNDVI (green normalized difference vegetation index) values across the various growth stages of rice. The application of treatment N4 resulted in the highest number of panicles m-2 (348.2 in TR, 376.8 in DSR), filled grains panicle-1 (74.55 in TR, 62.43 in DSR), and a 1000-grain weight of 26.92 g in TR and 26.76 g in DSR. The maximum yield (4.89 t ha-1) was obtained in transplanted rice at treatment N4 and, 8.15% yield reduction was noted in DSR for the same treatment, which was statistically equivalent to N3, but significantly superior to other N levels. Conversely, in DSR with RDN (120 kg N ha-1), the cost-benefit ratio surpassed that of TR by 16.96%, signifying DSR's adaptability for more profitable rice cultivation in the region. This research provides valuable insights into optimizing nitrogen management practices for TR and DSR, thereby enhancing rice crop performance and economic returns.